Leverage Multiplier, Interest Expense Ratio, Banking Ratio: Dampaknya Terhadap Return On Asset - Saeful Rizal, Deni; jamaludin, Ali; Hadi, Yulianto; Fitri; Evelini Handayani Sinaga, Vita; Sukmawati, Mega; Sidik Nusannas, Iman; Cintya Aprillia, Siti (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study was to examine the effect of Leverage Multiplier, Interest Expense Ratio, Banking Ratio on Return on Assets at BPR in Central Java in 2019-2023. The analytical method used is multiple regression analysis of panel data. The research results show that the average value of the Leverage Multiplier has decreased, which is balanced by a decrease in Return On Assets, which indicates that BPR has experienced a decrease in efficiency in generating profits from the assets it owns, despite reducing debt. The Interest Expense Ratio shows that interest costs are increasing, while the company's ability to generate profits is decreasing. Banking Ratio is decreasing in balance with ROA continuing to decline, this reflects a situation where BPR is more focused on increasing liquidity but this is not managed well